2016
DOI: 10.1126/science.aaf8430
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila insulin release is triggered by adipose Stunted ligand to brain Methuselah receptor

Abstract: Animals adapt their growth rate and body size to available nutrients by a general modulation of insulin-insulin-like growth factor signaling. In Drosophila, dietary amino acids promote the release in the hemolymph of brain insulin-like peptides (Dilps), which in turn activate systemic organ growth. Dilp secretion by insulin-producing cells involves a relay through unknown cytokines produced by fat cells. Here, we identify Methuselah (Mth) as a secretin-incretin receptor subfamily member required in the insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(148 citation statements)
references
References 30 publications
3
142
0
Order By: Relevance
“…One is the fat body, which produces and releases important regulators of dILP secretion in response to intracellular nutrient levels ( Fig. 6B; Geminard et al 2009;Rajan & Perrimon, 2012;Sano et al 2015;Delanoue et al 2016;Koyama & Mirth 2016). Interestingly, a recent study found that knocking down tor specifically in the fat body led to a decreased body size, leading the authors to suggest that Tor acts in the fat body to influence insulin signalling via an unknown mechanism (Jun et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…One is the fat body, which produces and releases important regulators of dILP secretion in response to intracellular nutrient levels ( Fig. 6B; Geminard et al 2009;Rajan & Perrimon, 2012;Sano et al 2015;Delanoue et al 2016;Koyama & Mirth 2016). Interestingly, a recent study found that knocking down tor specifically in the fat body led to a decreased body size, leading the authors to suggest that Tor acts in the fat body to influence insulin signalling via an unknown mechanism (Jun et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fat body-IPC feedback may be affected as well. However, the only factors known to mediate this process, Unpaired 2 (Rajan and Perrimon, 2012), DILP6 (Bai et al, 2012), and Stunted (Delanoue et al, 2016) have molecular masses of more than 5 kDa, and thus exceed the maximum mass of a putative neprilysin substrate (Oefner et al, 2000). Consequently, a direct regulatory influence of Nep4 on Unpaired 2, DILP6, or Stunted activity appears unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies identified growth-blocking peptides (GBP1 and GBP2) and Stunted (Sun) as AA-responding peptides secreted from the FB. These peptides also control the systemic growth of larvae by promoting the secretion of Drosophila insulin-like peptides (DILPs)1819. Nevertheless, AA-specific factors responsible for eliciting a behavioural change in feeding have so far eluded identification.…”
mentioning
confidence: 99%